Discourse Analysis of Fatwa Arguments in the Indonesian Ulema Council on Akidah and Religious Sects n 1975-2017 - Muhammad Ridwan; Syamsul Hadi; Amir Ma'ruf (Journal of Languages and Language Teaching, 2024)
Fatwas are a form of persuasive argumentative discourse. This paper aims to describe the superstructure and structure of fatwa arguments regarding Akidah and Religious Traditions. The source of this paper's data is all fatwas of the fatwa commission of the Indonesian ulema council from 1975 to 2017. The method used to collect data and manage data is the document method. Discourse analysis methods are used to analyze data. The discussion of superstructure aspects utilizes Ashqar theory (1976) while Walthon theory (2006) is used to examine the structure of fatwa argumentation. The superstructure aspect of fatwas is realized by the Fatwa Commission of the Indonesian Ulema Council differently. All fatwa texts have presented substantial elements but formal elements are not included. The structure of fatwa argumentation is understood by the format of the text. For fatwas in the format of decrees, premise markers are identified through the vocabulary of "pay attention", "read", "weigh", and "remember" while conclusion markers are presented with the vocabulary of "decide", "establish", and "fatwa". Directly formatted fatwa texts are identified through inference, but some texts lack a premise and inference structure.